Contingent Valuation and Willingness to Pay for Arbitrary Health Care Insurance: Time-Series Analysis - Mahmoud Kazemian; Hamideh Javadi Nasab (پژوهشهای اقتصادی, 2016)
Employees in the informal sector of the Iranian economy suffer from lack of access to various health insurance services. This research tries to assess the development of arbitrary health insurance schemes and households’ willingness to pay for health care premium for the low-income employees in the informal sector, totally aiming at universal coverage for the insurance scheme. This research is of statistical- analytic type, which uses contingent valuation questionnaire to estimate households’ willingness to pay for arbitrary health care premium subject to government financial contribution. To do this, it applies record data over the period 1987-2009. The regression analysis is used to determine households’ health care premium and public sector contribution. The research estimates the premium of the arbitrary health care insurance for the urban households in the first three deciles and determines the government contribution to this scheme. The estimated elasticities show that reduction in the government share in health care premium increases the effect of social- economic variables on households’ willingness to pay for health care premium. To achieve universal coverage in the arbitrary health insurance scheme for the low-income group requires providing appropriate data on variables affecting households’ willingness to pay through contingent valuation questionnaire. In addition, the administrative system for social health care insurance should be developed to the extent that low-income households can get access to insurance administrative services, and receive full information about annual households’ income and health expenditure, public sector contribution and monetary value for the arbitrary health insurance services.